Leading organizational change 1 - Dunham, Randall B. (Henry Stewart Talks, 2012)
Leading organizational change, Managing organizational change, Turning good ideas into good outcomes, The change management process, Stakeholder analysis, Stakeholder identification, Stakeholders facilitate organizational change, Potential stakeholder reactions to change, The causes of stakeholder reactions to change, Identify needed behaviour from stakeholders, Identifying gaps between desired and expected stakeholder reactions to change, Closing gaps between expected and desired stakeholder behaviors, Techniques to influence stakeholder reactions to change